Efektifitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Di Kabupaten Klaten Pada Materi Bencana Tanah Longsor Dengan Menggunakan Strategi Student Team Achievement Division ( STAD ) Terhadap Tingkat Kesiapsiagaan Siswa Di SMA Negeri 1 Karanganom - Nurlitasari, Istikomah; , Dr. Tjipto Subadi, M.Si (2016)
The aim of this research is to find out the effectiveness of teaching material in landslide disaster material in order to achieve student's preparedness level that use STAD strategy. The population in this research are students from VII, VIII abd IX class which amounts to 670 students. Technique used in research sampling is purposive sampling technique. Sampling technique uses certain consideration, this research uses considerations (1) students of SMA Negeri 1 Karanganyar, (2) students of X class who attend school disaster preparedness. The result obtained is the level of disaster teaching material effectiveness through STAD strategy. The result of average score shows that post test score in controlled class is 81% and the average score of post test in experimented class is 85%. This result signifies that the experimented class has better score and preparedness level than controlled class, so that the teaching material is more effective to be applied in experiment class by using STAD strategy. This research uses Wilxocon and Man-Whitney test that obtained probability score 0,000. With the result that, there is a significant influence and difference between controlled class and experimented class. Therefore, Ho is rejected and Ha is accepted.